Characteristics of non caloric dulcorants and their use in children - Calzada León Raúl; Altamirano Bustamante Nelly (Instituto Nacional de Pediatría, 2014)
This is a descriptive review of the elaboration routes, the physical and chemical characteristics, metabolism and clearance, sweetener level, residual flavor, maximal recommended ingestion, security levels and the assessment of growth and development problems in children (from newborns, including prematures, to the end of puberty), of the main no caloric edulcorants used in Mexico. The no caloric edulcorants included in this review are: aspartame, acesulfame-K, sucralose, sacarin, ciclamates, thaumatin, D- tagatose, estevia and alitame.